Risk Factors for Recurrent Pedatric Community Associated Clostridium difficile Infection. (4th October 2017) - Parmar, Deepika; Dang, Rebecca; Katz, Margot Miranda; Alabaster, Amy; Greenhow, Tara
Abstract: Background: As rates of pediatric community-associated (CA) Clostridium difficile infection (CDI) increase, additional research is needed to address the paucity of data in this cohort. Studies in pediatrics suggest concurrent antibiotics, CA CDI, malignancy, recent surgery, the number of antibiotic exposures by class and tracheostomy as independent risk factors for recurrent CDI (rCDI). Methods: This study was a retrospective review of the electronic health records of all children 1- 17 years with stool specimens sent for C difficile from January 1 st 2012 – December 31 st 2016 at Kaiser Permanente Northern California. Children with clinical symptoms consistent with CDI, confirmatory laboratory testing, no other identified causes of diarrhea, and community associated disease were defined as cases. Results: Of the 961 positive C. difficile cases from 2012 to 2016, 744 were community-associated. There were 558 total cases of CA CDI fitting case definition. Of these 507 were primary, 43 recurrence and 8 recurrence following recurrence. The incident rate of CDI was 17 per 100, 000 children. The overall rate of recurrence in our cohort was 8.5%. Race and having a diagnosis of inflammatory bowel disease (IBD) were statistically significant risk factors for rCDI. Compared with other races, we observed increased rates of rCDI in multi-racial and "other/unknown" children. Though not statistically significant, there appeared to be a correlation between the age subset of 2–5 years of age and developing rCDI. (Table) Conclusion: High suspicion for recurrence must be maintained in multi-racial or non-Caucasian, Hispanic, Asian, or African American children and those with underlying IBD for rCDI in children. Disclosures: All authors: No reported disclosures.